2017
DOI: 10.1530/eje-17-0314
|View full text |Cite
|
Sign up to set email alerts
|

Birth defects after use of antithyroid drugs in early pregnancy: a Swedish nationwide study

Abstract: MMI and PTU were associated with subtypes of birth defects previously reported, but the frequency of ATD exposure in early pregnancy was low and severe malformations described in the MMI embryopathy were rarely observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 36 publications
2
37
1
3
Order By: Relevance
“…Di Gianantonio et al (2001) did not find a statistically significant increase in risk of anomalies for MMI/CMZ exposure but did find two cases with anomalies consistent with the MMI/CMZ embryopathy. Similarly, Andersen et al (2017) did not find a statistically significant increase in the risk of anomalies for MMI/CMZ and PTU combined exposure but did find four cases with anomalies consistent with MMI/CMZ embryopathy.…”
Section: And Carbinazolementioning
confidence: 87%
See 4 more Smart Citations
“…Di Gianantonio et al (2001) did not find a statistically significant increase in risk of anomalies for MMI/CMZ exposure but did find two cases with anomalies consistent with the MMI/CMZ embryopathy. Similarly, Andersen et al (2017) did not find a statistically significant increase in the risk of anomalies for MMI/CMZ and PTU combined exposure but did find four cases with anomalies consistent with MMI/CMZ embryopathy.…”
Section: And Carbinazolementioning
confidence: 87%
“…PTU is associated with an increase in congenital anomalies less often than MMI/CMZ but some studies have noted an increased risk (Andersen, Lonn, Vestergaard, & Torring, 2017;Andersen, Olsen, Wu, & Laurberg, 2013;Howley et al, 2017;Leung, Yamamoto, Luca, Beaudry, & McKeen, 2015). A case study identified intestinal malrotation with congenital bands (Leung et al, 2015).…”
Section: Propylthioruacilmentioning
confidence: 99%
See 3 more Smart Citations